Implementasi Kurikulum Merdeka Materi Sistem Pemindah Tenaga Teknik Otomotif SMK N 2 Wonosari: Inggris, Indonesia - Nanang Wahyu Nugroho; Suhartanta Suhartanta (Journal of Automotive Technology and Education, 2025)
Abstract This research aims to find out: (1) The implementation of the Independent Learning Curriculum on Power Train System Material for Class XI Automotive Engineering at SMK N 2 Wonosari. (2) Supporting factors and inhibiting factors in implementing the Independent Learning Curriculum in Class XI Automotive Engineering Power Train System Material at SMK N 2 Wonosari. This research is a qualitative descriptive study. The subjects of this research were 2 (two) PCSPT teachers and 3 (three) class XI Automotive Engineering students taken using purposive sampling. Data collection techniques use interview and documentation techniques. This research uses the Miles and Huberman model data analysis technique. The results of the research show: (1) The implementation of the Independent Learning Curriculum on Power Train System Material for Class XI Automotive Engineering at SMK N 2 Wonosari has gone well. (2) Supporting factors, namely providing fun, comfortable and light learning conditions, providing various learning material references, availability of 60% practicum training objects, independent curriculum training workshops for teachers, and guest teachers for the P5 program. The inhibiting factors are the material load which is too extensive for students, the adequacy of practicum media which is not yet ideal, and the Wifi internet speed which is not yet able to accommodate all students.   Abstrak Tujuan penelitian ini adalah untuk mengetahui: (1) Implementasi Kurikulum Merdeka Belajar pada Materi Sistem Pemindah Tenaga Kelas XI Teknik Otomotif di SMK N 2 Wonosari. (2) Faktor pendukung dan faktor penghambat dalam Implementasi Kurikulum Merdeka Belajar pada Materi Sistem Pemindah Tenaga Kelas XI Teknik Otomotif di SMK N 2 Wonosari. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah 2 (dua) guru PCSPT dan 3 (tiga) siswa kelas XI Teknik Otomotif berjumlah yang diambil dengan cara purposive sampling. Teknik pengumpulan data menggunakan teknik wawancara dan dokumentasi. Penelitian ini menggunakan teknik analisis data model Miles and Huberman. Hasil penelitian menunjukkan: (1) Implementasi Kurikulum Merdeka Belajar pada Materi Sistem Pemindah Tenaga Kelas XI Teknik Otomotif di SMK N 2 Wonosari telah berjalan dengan baik. (2) Faktor pendukung yaitu pengkondisian pembelajaran yang menyenangkan, nyaman, dan ringan, pemberian referensi materi belajar yang beragam, ketersediaan training object praktikum yang sudah 60%, workshop pelatihan kurikulum merdeka untuk guru, dan guru tamu untuk program P5. Faktor penghambat yaitu beban materi yang terlalu luas untuk siswa, ketercukupan media praktikum yang belum ideal, dan kecepatan internet Wifi yang belum mampu mengakomodir seluruh siswa.